Leaf Cuticular Transpiration Barrier Organization in Tea Tree Under Normal Growth Conditions - Chen, Mingjie; Zhang, Yi; Kong, Xiangrui; Du, Zhenghua; Zhou, Huiwen; Yu, Zhaoxi; Qin, Jianheng; Chen, Changsong (Frontiers in Plant Science, 2021)
The cuticle plays a major role in restricting nonstomatal water transpiration in plants. There is therefore a long-standing interest to understand the structure and function of the plant cuticle. Although many efforts have been devoted, it remains controversial to what degree the various cuticular parameters contribute to the water transpiration barrier. In this study, eight tea germplasms were grown under normal conditions; cuticle thickness, wax coverage, and compositions were analyzed from the epicuticular waxes and the intracuticular waxes of both leaf surfaces. The cuticular transpiration rates were measured from the individual leaf surface as well as the intracuticular wax layer. Epicuticular wax resistances were also calculated from both leaf surfaces. The correlation analysis between the cuticular transpiration rates (or resistances) and various cuticle parameters was conducted. We found that the abaxial cuticular transpiration rates accounted for 64–78% of total cuticular transpiration and were the dominant factor in the variations for the total cuticular transpiration. On the adaxial surface, the major cuticular transpiration barrier was located on the intracuticular waxes; however, on the abaxial surface, the major cuticular transpiration barrier was located on the epicuticular waxes. Cuticle thickness was not a factor affecting cuticular transpiration. However, the abaxial epicuticular wax coverage was found to be significantly and positively correlated with the abaxial epicuticular resistance. Correlation analysis suggested that the very-long-chain aliphatic compounds and glycol esters play major roles in the cuticular transpiration barrier in tea trees grown under normal conditions. Our results provided novel insights about the complex structure–functional relationships in the tea cuticle.